Berburu Babi Sebagai Sistem Mata Pencaharian Tradisional pada Orang Bali di Desa Kasimpa Jaya Kabupaten Muna Barat - La Acok, La Acok; Jalil, Abdul (Jurusan Antropologi Fakultas Ilmu Budaya Universitas Halu Oleo, 2024)
Study This aim For know And describe culture hunt pig in system eye livelihood with form group? social to Balinese people in the village Kasimpa Jaya District South Tiworo Regency West Muna. The theory used in study This is structural function Redcliffe Brown (1955). Technique deep data collection study This with use method study field conditional ethnography? with observation involved And interview deep . Technique analysis used? is descriptive qualitative . Results study This showing that the reason why Balinese people hunt pig as Wrong One element frequent culture? done to Balinese people in the village Kasimpa Jaya District Tiworo south Regency West Muna. With cultures hunting pig Balinese people think so matter scattered is something system eye livelihood they For endure life And as Wrong One frequent hobby? done by inner Balinese society daily they. Hunt pig Already become frequent habit? done in scope public And is something inheritance from created ancestors? as tool or system eye livelihood traditional for Balinese people to endure life And add economy in family . With exists something culture or frequent habits? done in activity hunt pig give birth to values contained culture? in hunt pig like mark Work The same And mutual work together . In the process of hunting pig there is a number of known stages? by Balinese people in the village Kasimpa Jaya for support walking activity hunt pig ie preparation equipment For hunting, period member hunt formed pig? in something group structured social? And task member hunting people? pig . Stages the is part from strategy And frequent technicalities? happen in the process of hunting pig forest For Can make it easier get objective or results in the process of hunting pig.